Pengaruh Proactive Personality, Core Self-Evaluation Terhadap Kinerja Karyawan Dimediasi Work Engagement - Anugrahito, Dimas; Muafi, Muafi (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the influence of proactive personality and core self-assessment on employee performance in work mediation at startups in BLOCK71 Yogyakarta. The population in this study was 97respondents, which is then chosen usinga purposive sampling technique with a total sample of 78 respondents who were startup employees at Block71 Yogyakarta. This research uses quantitative methods with a questionnaire. The analytical test tool used in this study is SmartPLS v.3.0 with SEM (Structural Equation Modeling) analysis method.The results of data analysis in this study indicate that:(1) proactive personality has a positive effect on work engagement (2) Core self-evaluation has a positive effect on work engagement (3) Job involvement does not affect employee performance (4) Core self -evaluation has a positive effect on employee performance (5) Proactive personality has a positive effect on employee performance (6) Proactive personality has a positive effect on employee performance mediated by work engagement (7) Core self-evaluation has a positive effect on employee performance mediated by work engagement. Of the seven existing hypotheses, the third hypothesis is rejected and the other hypothesis is accepted.